Proyecto de factibilidad para la Implementación de una Empresa Productora y Comercializadora de zumo a base de la fruta Camu Camu, en la Ciudad de Loja - Villalta Jaramillo, Victor Emilio (2016)
Ecuador is rich in diversity of fruits is concerned, but some have not yet been industrialized including camu camu, it contains large amounts of vitamin C, equivalent to almost 40 times that of orange pulp and it is used for treatment of different diseases. It is little known in the market, there is little incentive for farmers to grow it. The purpose of this study is to raise awareness and encourage the cultivation of this exotic fruit from the Amazon, this research seeks to measure the feasibility will be the implementation of a producer and marketer of juice from the fruit camu camu, in the city of Loja. For the aforementioned reasons the proposed theme is "Project feasibility for implementing a producer and marketer of juice-based company camu camu fruit in the city of Loja"; seeking to measure the impact that investment promotes the welfare of society by meeting consumer needs and generation of jobs, from this context has developed an investment project it has a useful life of 5 years . In the present project objectives as general where they were met; determine the "Feasibility Study for the implementation of a producer and marketer of juice-based company camu camu fruit in the city of Loja", so that will generate returns to investors. For proper development of work methods such as inductive, deductive and descriptive were used, also the techniques of observation, survey was applied to the families of the city of Loja giving a total of 381 surveys were used, 321 6 surveys were also applied local (shops, pantries and supermarkets) according to the data obtained in the town of Loja. With the information obtained in the surveys are presented in the discussion where they developed the different studies that make up the project, market research unmet demand for 339,832 liters of juice in the first year was obtained. With the data obtained from market research we proceeded to the preparation of the technical study, which made it possible to determine the used capacity is 166,400 liters of juice (332,800 units pint) and which was used 23.7% of the installed capacity a year. It is important to note that the company will be located in the city of Loja, district Time at Holland between Greece and Av. Eugenio Espejo, also possible to determine the necessary resources for the operation of the production unit, such as machinery and equipment, engineering project, physical distribution. The administrative study produced the legal and functional organizational structure with its structural, positional and functional organization and functions manuals for each of the posts. In the financial study of the project, the same one that requires an initial investment of $ 64.010,50 of which 61% will be financed with equity and 39% by the National Development Bank with an interest rate of 10%. The total production cost for the first year is $ 291,839.23 the same as projected for the five-year life of the project with 5% inflation by economic instability, the unit sales price for first year is $ 1.05 with a profit margin of 20% earning revenue of $ $ 350,207.08, breakeven in terms of installed capacity is 39.34%, 7 depending on sales is $ 137,781.55 and according to the production of 130,933.11 units pint juice. In the profit and loss a profit of $ 34,819.98 in the first year will be achieved. The financial evaluation project feasibility is established, where the cash flow that allowed us to determine the Net Present Value of $ 102,129.28 which ensures an increase in the value of the company at the end of the lifetime of the project was completed, the internal rate of return for the project is 58.31% by which the project is accepted as it is higher than the rate of opportunity cost of money, the Capital Recovery Period is 1 year 7 months and 16 days, Benefit Cost ratio is 1.20 indicating that for every dollar invested 0.20 cents profit will be obtained as to sensitivity analysis of the project supports increased costs and decreased 10.46% in income 8.71%. So it is concluded that the project is feasible and can be put in place. After completing the studies findings was determined with the respective recommendations according to the results obtained in developing the